Cardiodiabesity: Epidemiology, resource and economic impact - Duy Do; Tiffany Lee; Calie Santana; Angela Inneh; Urvashi Patel (American Journal of Preventive Cardiology)
Objective: To assess i) the epidemiology of cardiodiabesity, ii) its association with healthcare resource utilization and cost of care, as well as iii) provide recommendations for its management. Methods: A cohort study of insured adults with early-stage and/or active cardiodiabesity from January 2019 to December 2021 identified through a longitudinal, and de-identified medical and pharmacy claims database was conducted. All patients were followed for one year through December 2022. Conditions include cardiovascular disease, prediabetes, Type 2 diabetes (T2D), chronic kidney disease (CKD), overweight and/or obesity. Rates of progression from early-stage cardiodiabesity to active cardiodiabesity and/or advanced cardiodiabesity with complications; frequency of emergency department, inpatient and outpatient visits; as well as total cost of care over one year were analyzed. Results: A total of 3,273,813 and 1,628,407 patients had at least one of the comorbid conditions for early-stage and active cardiodiabesity, respectively. Among those with all early-stage cardiodiabesity conditions, 27.4 % progressed to active cardiodiabesity, while 88.4 % of those with all active cardiodiabesity conditions progressed to complications within one year. Predictors of progression from early-stage to active cardiodiabesity were hypertension (OR: 2.31, 95 % CI: 2.29–2.33, p < 0.001), hyperlipidemia (OR: 1.77, 95 % CI: 1.76–1.79, p < 0.001), CKD stages 1 and 2 (OR: 1.74, 95 % CI: 1.69–1.79, p < 0.001), prediabetes (OR: 1.64, 95 % CI: 1.63–1.66, p < 0.001) and living in areas with very high social needs (OR: 1.25, 95 % CI: 1.23–1.26, p < 0.001). Significant predictors of progression from active cardiodiabesity to complications were T2D (OR: 1.88, 95 % CI: 1.81–1.96, p < 0.001), CVD (OR: 1.47, 95 % CI: 1.44–1.51, p < 0.001), CKD stages 3 and 4 (OR: 1.37, 95 % CI: 1.34–1.41, p < 0.001) and obesity (OR: 1.29, 95 % CI: 1.26–1.32, p < 0.001). Average total cost of care increased significantly among those who progressed from one disease phase to the next (p < 0.05). Conclusions: Cardiodiabesity is deadly and rapidly progressive with substantial economic burden on the healthcare system. However, it is preventable. Innovative approaches to better understand the holistic impact of cardiodiabesity on total cost of care, early intervention or management to halt disease progression and promote equity, as well as decrease resource utilization are needed.